Is ProBNP a New Marker for Predicting Intrauterine Growth Restriction? - Eroğlu, Hasan; Tonyalı, Nazan Vanlı; Orgul, Gokcen; Biriken, Derya; Yucel, Aykan; Yazihan, Nuray; Uygur, Dilek (Zeitschrift für Geburtshilfe und Neonatologie, 2021)
Purpose To evaluate the usability of first-trimester maternal serum ProBNP levels in the prediction of intrauterine growth restriction (IUGR). Methods In this prospective study, blood samples taken from 500 women who applied to our polyclinic for routine serum aneuploidy screening between the 11–14th gestational weeks were centrifuged. The obtained plasma samples were placed in Eppendorf tubes and stored at −80+°C. For the final analysis, first-trimester maternal serum ProBNP levels of 32 women diagnosed with postpartum IUGR and 32 healthy women randomly selected as the control group were compared. FGR was defined as estimated fetal weight below the 10th percentile for the gestational age.Results The mean ProBNP levels were statistically and significantly higher in the women with intrauterine growth restriction (113.73±94.69 vs. 58.33±47.70 pg/mL, p<0.01). At a cut-off level of 50.93, ProBNP accurately predicted occurrence of IUGR (AUC+= 0.794 (95% confidence interval 0.679–0.910), p+= 0.001) with sensitivity and specificity rates of 78.1 and 69.0%, respectively. Conclusion First-trimester serum ProBNP level was significantly higher in women who developed IUGR compared to healthy controls. First-trimester ProBNP level can be used as a potential marker to predict the development of IUGR in pregnant women.
Keywords: Pregnancy; intrauterine growth restriction; placenta; first trimester; ProBNP